Don't know what to write written / Wan Muhammad Aiman - Aiman, Wan Muhammad
In the class project, students write poems using the poetry prompts given. The activities with poetry prompts develop learner's independence and confidence to read aloud, perform, write, and experiment with language. Besides the benefits that are meaningful on a more personal level such as emotional and intellectual, poetry prompts assist learners to practice for strengthening one’s writing skills excellently. Through poetry writing, one’s gain command of language, cultivate a robust and expressive vocabulary, master literary devices, and learn to work in imagery.